Multiple-input multipleoutput concept on frequency modulated continuous wave radar using beat averaging method for maritime application / Asiah Maryam Md Noor - Md Noor, Asiah Maryam (2023)
Finding the ideal performance of a maritime radar can be challenging due to the large sea spikes and the required day-to-night operation for maritime surveillance. The employment of multiple-input multiple-output (MIMO) radar concept in frequency modulated continuous wave (FM-CW) radar is intended to improve the performance of maritime radar due to their advantages, among others, in terms of better accuracy and low output power. Nevertheless, there are minimal number of works that investigate in detail, the MIMO processing method at the receiver side. Furthermore, reports on experimental result on MIMO-FMCW is rarely reported. Existing method requires complex processing due to multiple signals used in MIMO and Fast Fourier Transform (FFT) computation in the MIMO FM-CW processing at the receiver. Therefore, the objective of this thesis is to propose an alternative post-processing scheme for the MIMO FM-CW radar system using beat averaging method to reduce the computational complexity of the radar system, and analyse the performance of the proposed MIMO FMCW radar scheme, through numerical simulations and experimental evaluation. This method uses multiple frequency diverse FM-CW signals in transmission where multiple beat signals produced during target detection was averaged before FFT computation. The proposed method is initially studied in a numerical simulation where several schemes of MIMO radar was evaluated before it is compared with the performance of the single radar system, and the existing post-processing method of MIMO FM-CW radar. The performance evaluation was studied in terms of probability of ranging errors and computational complexity before the results were further validated through experiment. The results of the study have showed an improvement of probability of range error when using MIMO FM-CW radar system compared to conventional FMCW radar system. In addition, the proposed scheme using beat averaging method also outperforms the existing MIMO-FMCW using spectrum averaging, by approximately 2 dB in signal-to-noise ratio to achieve similar performance. The proposed scheme also comes with a lower computational complexity compared to the spectrum averaging method. Therefore, the proposed scheme is considered a good alternative processing scheme to implement a MIMO concept in FM-CW systems, providing an advancement towards the realisation of the said system.